2019
DOI: 10.1109/access.2019.2950539
|View full text |Cite
|
Sign up to set email alerts
|

A Quad Motifs Index for Directed Link Prediction

Abstract: Network motif is a sub-graph pattern may reflect structure functions or reveal underneath mechanics. Some scholars have used triadic motifs for link prediction and achieve convincing results. But most of them ignore the effectiveness of quad motifs in calculating the similarity of two endpoints. In this article, a new method based on quad motifs is proposed. Two winner motifs are chosen among 199 sub-graphs. Local information of motifs is also taken into consideration. Experiments on nine real networks show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…They proposed that the bi-directional link contains more network information, and found that a pair of nodes with bi-directional links has greater probability to connect to the common neighbours with bi-directional links. Hu et al [10] considered the effectiveness of quad motifs in calculating the similarity between nodes in the directed network, and defined closed quad, relative open quad, no-crossing closed quad and quad motifs. Li et al [11] defined a community relationship strength index (CRS) to estimate the closeness between communities, and proposed a link prediction framework based on node similarity and community information.…”
Section: A Similarity Index-based Prediction Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…They proposed that the bi-directional link contains more network information, and found that a pair of nodes with bi-directional links has greater probability to connect to the common neighbours with bi-directional links. Hu et al [10] considered the effectiveness of quad motifs in calculating the similarity between nodes in the directed network, and defined closed quad, relative open quad, no-crossing closed quad and quad motifs. Li et al [11] defined a community relationship strength index (CRS) to estimate the closeness between communities, and proposed a link prediction framework based on node similarity and community information.…”
Section: A Similarity Index-based Prediction Methodsmentioning
confidence: 99%
“…where S is the number of nodes in the hidden layer, m is the input length of the model, n is the output length of the model, and a is an integer within [1], [10]. Considering the size of the sample set and reducing the time complexity of model training, this paper selects equation (8) to determine the number of nodes in the hidden layer.…”
Section: ) the Number Of Nodes In The Hidden Layermentioning
confidence: 99%
See 2 more Smart Citations
“…By counting the numbers of 4 different directed 2-paths and 8 different directed 3-paths around a pair of nodes, the paper finds out that a link has a higher probability of appearing if it could generate more bi-fan subgraphs [213]. Very similar to the idea of potential theory, the quad motifs index proposes to count particularly three types of directed open-quadriad (3-paths) subgraphs: two of them are the bases for bi-parallel subgraphs and the other one is for bi-fan [87]. Specifically, the quad motifs index of a pair of nodes đť‘– and đť‘— is defined as:…”
Section: -Hop Neighboursmentioning
confidence: 99%